Pemilihan Rekomendasi Rumah Makan Vegetarian Menggunakan Metode AHP - Tandy, Henry; Hamidi, Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
Purchasing activities are activities that need to be carried out by the community to meet the needs of life. Vegetarian restaurants are one of the businesses that sell food needs. However, during the purchase process there is a level of satisfaction from consumers. These levels are influenced by various factors or criteria. The purpose of this study is to measure and rank the recommended vegetarian restaurant rankings and the criteria that affect the purchase process using the Analytical Hierarchy Process (AHP) method. The results of this study are Cafe Abang restaurant (A1) with a weight value of 0.379, the second place is the Kedai Bo Bak restaurant (A3) with a weight value of 0.25, the Sweet Veggie restaurant (A2) is in third place with a weight value of 0.191, and RM. Healthy Vegetarian (A4) with a weight value of 0.18. While the criteria for food and beverage menu prices (C3) with a weight value of 0.311, the second place is the operational time criterion (C4) with a weight value of 0.228, the third place is with the restaurant location distance criterion (C5) with a weight value of 0.216, the fourth place is with the number of food and beverage menu variants (C1) with a weight value of 0.153, and ranked fifth with the criterion of the number of restaurant facilities (C2) with a weight value of 0.092.